The impact of lean management on frontline healthcare professionals: a scoping review of the literature - Zeyad Mahmoud; Nathalie Angelé-Halgand; Kate Churruca; Louise A. Ellis; Jeffrey Braithwaite (BMC, 2021)
Abstract Background Lean management practices are increasingly used in hospitals. However, their impacts on staff have not been systematically synthesised. This scoping review aims to synthesise the evidence on the effects of Lean Management practices on frontline healthcare professionals. Methods A search was conducted in February 2020 on multiple databases to identify relevant sources. Studies had to satisfy the following inclusion criteria to be considered: published in English or French, peer-reviewed, empirical, studied the use of Lean in a healthcare setting and focused on its impacts on frontline workers. The studies included were heterogeneous in terms of participants. Findings were coded and classified using a thematic analysis. The quality and methodological rigour of the reviewed articles were assessed to establish a level of confidence in their findings. Results Of 998 identified articles, 17 were included in the review. The findings were coded into four themes: (1) Morale, motivation and job satisfaction (n = 9, 2) work intensification, job strain, anxiety, stress and dehumanisation (n = 7, 3) teamwork, communication and coordination (n = 6); and (4) learning, innovation and personal development (n = 3). Overall, the articles reported positive (n = 11), negative (n = 3) and mixed (n = 3) impacts of Lean on frontline healthcare professionals. Conclusion This review is the first to synthesise and highlight the gaps in the existing literature examining the impacts of Lean on frontline health professionals. The review revealed a range of both positive, negative and mixed effects, and points to the need for more empirical research to identify the underlying reasons leading to these outcomes.